Job Analysis as Basic Human Resources Management for Human Resources Placement (study in the "Model" of Public Elementary School - City of Malang) - Palupi, Puspita Auditya Sotya (Jurnal Administrasi Publik, 2014)
Abstrak : Analisis Jabatan sebagai Dasar Manajemen Sumber Daya Manusia untuk Penempatan Sumber Daya Manusia (studi di Sekolah Dasar Model - Kota Malang). Masih ada ketidakcocokan antara latar belakang pendidikan dan beban kerja yang dipercayakan pada sumber daya manusia. Beban kerja masih belum jelas. Pegawai Negeri Sipil sudah diatur dalam UU no 14 tahun 2005, tetapi bagi karyawan dan guru tidak tetap masih bergantung pada kebijakan sekolah. Dengan penelitian kualitatif dan analisis deskriptif, hasilnya adalah beban kerja bagi guru honorer bergantung pada jam kerja yang disediakan sekolah. Â Karena masih ada posisi yang belum diisi oleh orang yang berpengalaman maka prinsip kemanusiaan harus dipakai. sperti yang sudah dijelaskan pada skripsi ini. Tetapi masih ada banyak kriteria yang seharusnya dipenuhi dalam menempatkan sumber daya manusia.Kata kunci: Analisis Jabatan, Analisis Beban Kerja, Manajemen Sumber Daya ManusiaAbstract : Job Analysis as Basic Human Resources Management for Human Resources Placement (study in the â€œModelâ€ of Public Elementary School â€“ City of Malang). There are still mismatch between educational background and workload entrusted to human resources. Workload is still unclear. If civil servants already regulated in Act no 14 in 2005 year, then for temporary staff depending on school policy in determining the workload. With qualitative research and descriptive analysis, the result is a load of work on honorary staff depending on the number of hours provided by the school and also the amount of workload associated with the provision of fringe benefits. The aim is to know are the human resources balance with workload. In addition there are some positions not filled by less experienced people in the field. Humanitarian principles used in this placement. In addition to humanitarian principles also explained also the criteria used in the placement of employees in this thesis. Again, there are several criteria that should be fixed benchmark in placing employees but not yet used. Â  Key word: Job Analysis, Work-load Analysis, Human Resources Management